The Predicative Infinitive Construct in Phoenician and Punic - Fofliger, Ophir Carmel; Cohen, Ohad; Zewi, Tamar (Folia Orientalia, 2025)
This study examines the prevalent predicative utilization of the infinitive construct following the preposition l- (=l-+IC) in Phoenician, Punic and Neo-Punic. It compiles predicative l-+IC constructions through the different historical phases of Phoenician, providing a comprehensive insight into its use. Two distinct grammaticalization pathways of the l-+IC construction are suggested: obligatory attachment of the preposition l- to the IC, and its transition from adverbial to predicative usage. The varied modal functions of the independent predicative l-+IC construction are traced to these two primary processes. Widespread predicative use of the l-+IC in Late Biblical Hebrew and Qumran Hebrew is believed to echo Phoenician constructions—an outcome of the historically intensive language contact situation—underscoring its central role within the Phoenician linguistic structure.